Light Aviation And Flight Safety: Monitoring System For Unpressurised Cabins. Flight And Physiological Data Acquisition - Andre Marques; Sara Zorro; Luís Patr\~ao; Jorge Silva; Miguel Castelo-Branco (European Regional Science Association (ERSA), 2012)
The majority of light aviation aircrafts cabins are unpressurised and this may pose risks for the safety of both pilots and passengers. As altitude increases partial oxygen pressure decreases and this situation may lead to early stages of hypoxia affecting pilot's capabilities to perform simple tasks. These factors combined in several ways may affect significantly the capability of a pilot to conduct a safe flight. Some work has been developed in this area and results show that even small changes in altitude can decrease pilot's oxygen level significantly. Thus, as pilot's behaviour and flying capabilities are affected, flight safety is compromise too. This work is generally focused on the acquisition and study of flight operational and physiological data that may affect pilot's capabilities and thus flight safety. To perform such objectives data acquired from the aircraft contains several items such as geographic coordinates, attitude, altitude, speed, g-load, heading, absolute pressure and temperature inside the cabin; also data acquired from the pilot contains several parameters such as cerebral oximetry, electroencephalography (EEG) and electrocardiography (ECG). As pilot's own safety and comfort are important issues we developed a portable system that may be installed and operated in a safe and ergonomic way inside any light (small) aircraft cabin. Also this equipment is flexible enough so that it may be used inside a hypobaric chamber or in a flight simulator to test, prior a real flight, some specific pilot's reactions to different flight scenarios. The specific objective of this paper is to report the acquisition, processing and monitoring of flight data collected directly and in real time from both the aircraft and the pilot, so it may be analysed to determine pilot's major physiological changes facing different flight scenarios and the consequents alterations of his flying capabilities. Legislation for pilot licensing is quite similar all over Europe, and in practice it is not capable to prevent such in-flight individual performance problems. Taking in account the results of this work we also sustain the basis for a revision of the actual European legislation for pilot licensing, thus improving flight safety.
Keywords: 330